Karakteristik Sifat Fisik Tanah dan Sistem Jaringan Tata Air di Desa Bandar Jaya Jalur 25 Air Sugihan - Bakri, Bakri; S, Momon.; Karimudin, Y. (Seminar Nasional Lahan Suboptimal, 2018)
Bakri et al, 2019. Characteristics of Soil Physical Properties and Water Management Network Systems In Bandar Jaya Village, Primer 25 Air Sugihan. pp. 138-145.The development of the potential of tidal land for annual crops, especially rice plants, is very needed information on the physical properties of the soil and the systems of water management. There are two conditions in Bandar Jaya Village, namely the use of tidal water in the dry season and water discharge during the rainy season. The objective of this research was to determine characteristics of soil physical properties and water management network systems. The condition is intended to not lack water in the dry season and there will be no flooding in the rainy season. Soil sampling activity was carried out intentionally on the fourth tertiary plot of Primer 25 Air Sugihan in Bandar Jaya Village. The physical condition of the soil at a depth of 0 - 30 cm BD is low (0.67 g / cm3), the Total Pore is high (77%), while in the depth of the soil 30 - 60 cm BD 0.74 g/cm3, and Total Pore 73 %. At soil depth> 60 cm BD 0.98 g / cm3 and Total Pore 64%. Dusty clay texture. This soil condition can support plant growth and production. Water management network is built with a pair comb system, tertiary canals have been equipped with sluice gates and modified goose neck sluice, so that water management can be carried out to support cropping indices.